Excessive Iodine Promotes Pyroptosis of Thyroid Follicular Epithelial Cells in Hashimoto's Thyroiditis Through the ROS-NF-κB-NLRP3 Pathway - Liu, Jiameng; Mao, Chaoming; Dong, Liyang; Kang, Ping; Ding, Chao; Zheng, Tingting; Wang, Xuefeng; Xiao, Yichuan (Frontiers in Endocrinology, 2019)
Hashimoto's thyroiditis (HT) is a common autoimmune thyroid disease. In recent years, increasing evidence has proven that the incidence of HT is associated with the excessive iodine intake of the body. In the present study, we measured the status of pyroptosis in thyroid tissues from patients with HT and the effects of excessive iodine on the pyroptosis in thyroid follicular cells (TFCs), in an attempt to illuminate the effects of iodine excess on the development of HT disease. Our results showed that increased pyroptosis occurred in the thyroid tissues of HT patients and that an increase in pyroptosis activity in TFCs was primed by excessive iodine in vitro. This process was mediated by reactive oxygen species (ROS) and activation of the NF-κB signaling pathway. In addition, excessive iodine caused NLRP3 inflammasome activation in TFCs, which promoted TFC pyroptosis. Moreover, the release of interleukin-1β (IL-1β) was closely linked to pyroptosis activation. Taken together, our results suggested that excessive iodine contributed to aberrant activation of pyroptosis in TFCs, which could be a pivotal predisposing factor for HT development.